Statistical and spectral analysis of wind over a strategic location. Issue 9 (11th August 2022) - Srivastava, Nishi; Divyam, Jaya; Ghosh, Upamanyu; Priya, Madhu; Saxena, Nisheeth; Kumar, Manoj
Abstract: In the present work, we explored the inherent characteristics of the wind over a complex terrain site 'Ranchi' situated near a strategic location of the monsoon trough with various mathematical and statistical tools, i.e., time-series analysis, Fast Fourier transform (FFT), FFT coefficients, wavelet decomposition, and Weibull distribution. The time-series analysis showed a rapid day-to-day variability with a seasonal variation with a peak during summer. Fourier coefficients were concentrated for the winter/post-monsoon, indicating lower wind conditions, while wide spreads of the points indicate agility, i.e., high wind during the summer. The spectral features obtained using FFTs infer that wind has a prominent peak at a frequency f =0.00106724 (day −1 ) and f =0.00266809 (day −1 ). The power spectrum and wavelet decomposition show that the prominent frequencies correspond to yearly, eight, six, and four months. Weibull probability density function, cumulative probability distributions, and probability profiles are studied. Results show that the Weibull distribution function reasonably models the probability distribution of daily wind speed. Weibull scale parameter varied between 0.26 and 1.33 m/s, and the shape parameter ranged between 1.09 and 2.88. Results from various analyses indicate that the seasonal variation of wind speed over Ranchi is mainly associated with the development of monsoon trough over the site. HIGHLIGHTS: Inherence characteristics of wind over a site in the Indian trough region have been investigated. The highest mean speeds are observed just before the onset of monsoon and the lowest just after its departure in the post-monsoon season. Shape and scale parameters indicate more robust and variable winds in summer. Seasonal wind speed variation over Ranchi is mainly associated with the development of monsoon trough. Graphical Abstract